Gene regulatory networks controlling hematopoietic progenitor niche cell production and differentiation in the Drosophila lymph gland. - Tokusumi, Y.; Tokusumi, T.; Shoue, D.A.; Schulz, R.A. (PLoS ONE, 2012)
Hematopoiesis occurs in two phases in Drosophila, with the first completed during embryogenesis and the second accomplished during larval development. The lymph gland serves as the venue for the final hematopoietic program, with this larval tissue well-studied as to its cellular organization and genetic regulation. While the medullary zone contains stem-like hematopoietic progenitors, the posterior signaling center (PSC) functions as a niche microenvironment essential for controlling the decision between progenitor maintenance versus cellular differentiation. In this report, we utilize a PSC-specific GAL4 driver and UAS-gene RNAi strains, to selectively knockdown individual gene functions in PSC cells. We assessed the effect of abrogating the function of 820 genes as to their requirement for niche cell production and differentiation. 100 genes were shown to be essential for normal niche development, with various loci placed into sub-groups based on the functions of their encoded protein products and known genetic interactions. For members of three of these groups, we characterized loss- and gain-of-function phenotypes. Gene function knockdown of members of the BAP chromatin-remodeling complex resulted in niche cells that do not express the hedgehog (hh) gene and fail to differentiate filopodia believed important for Hh signaling from the niche to progenitors. Abrogating gene function of various members of the insulin-like growth factor and TOR signaling pathways resulted in anomalous PSC cell production, leading to a defective niche organization. Further analysis of the Pten, TSC1, and TSC2 tumor suppressor genes demonstrated their loss-of-function condition resulted in severely altered blood cell homeostasis, including the abundant production of lamellocytes, specialized hemocytes involved in innate immune responses. Together, this cell-specific RNAi knockdown survey and mutant phenotype analyses identified multiple genes and their regulatory networks required for the normal organization and function of the hematopoietic progenitor niche within the lymph gland.